LE KALINGA, Tambour Enseigne du royaume et de la dynastie des rois Banyiginya du Rwanda, by Marcel Pauwels, W. F.; pp. 221-256, 17 illustrations and one map. 2. LA MUSIQUE ET LES INSTRUMENTS de la Musique des Noirs de la region de Baudoinville (Congo), by Joseph Weghsteen, W. F.; pp. 85-112, 25 illust. and 15 songs. Both reprints from The Annals of the Pontifical Missionary Museum of Ethnology, Vatican City, Vol. XXVI, 1962, and Vol. XXVIII, 1964, respectively - Basil, Brother (International Library of African Music, 1965)
pages: 84-85
Keywords: Central Africa; African Music; Rwanda